Ethnomedicinal plants uses for the treatment of respiratory disorders in tribal District North Waziristan, Khyber Pakhtunkhawa, Pakistan - Rehman, Sabith; Iqbal, Zafar; Qureshi, Rahmatullah; Shah, Ghulam Mujtaba; Irfan, Muhammad (Ethnobotany Research and Applications, 2023)
Background: The current survey aimed to assess the traditional knowledge and use of therapeutic plants to treat various respiratory disorders by traditional healers. The local communities of District North Waziristan are reliant on therapeutic plant species for their primary health care needs. Methods: Ethnobotanical data were collected through semi-structured interviews. A sum of 130 informants (107 male and 23 female) selected randomly. Ethnobotanical data was quantitatively analyzed by using Use Value (UV), Relative Citation of Frequency (RFC), and Fidelity Level (FL). Results: A total of 56 plants related to 32 plant families were recorded which were used to cure 24 various respiratory disorders. Lamiaceae (7 species) was the most prevalent plant family, followed by Asteraceae (5 species), Moraceae and solanaceae (4 species) each, 8 families have (2 species each), while the remaining 20 families has only (1 species each).The dominant growth form was herbs (53.57%), while leaves (28.57%) were the leading plant part used in remedies preparation for respiratory disorders. The dominant method of medications preparation was decoctions (42.86%), which were all administered orally. The plant species with highest use values were Ephedra procera (0.87), followed by Morus nigra (0.86), while the highest RFC values were recorded for Ephedra procera (0.36), followed Cydonia oblonga (0.35), Morus nigra (0.34). The therapeutic plant species with maximum use values reported in the survey may indicate the possible presence of important bioactive compounds which need a search for potential new drugs to treat various respiratory disorders. Conclusions: The study accomplishes that indigenous communities yet prefer therapeutic plants species over allopathic drug for curing different disorders. However this valuable traditional information is limited to elder people. So, attention is required to conserve this traditional knowledge.